Distributed Control Architecture - Trevor Rawlings (2009)
This document describes the development and testing of a novel Distributed Control Architecture (DCA). The DCA developed during the study is an attempt to turn the components used to construct unmanned vehicles into a network of intelligent devices, connected using standard networking protocols. The architecture exists at both a hardware and software level and provides a communication channel between control modules, actuators and sensors. A single unified mechanism for connecting sensors and actuators to the control software will reduce the technical knowledge required by platform integrators and allow control systems to be rapidly constructed in a Plug and Play manner. DCA uses standard networking hardware to connect components, removing the need for custom communication channels between individual sensors and actuators. The use of a common architecture for the communication between components should make it easier for software to dynamically determine the vehicle s current capabilities and increase the range of processing platforms that can be utilised. Implementations of the architecture currently exist for Microsoft Windows, Windows Mobile 5, Linux and Microchip dsPIC30 microcontrollers. Conceptually, DCA exposes the functionality of each networked device as objects with interfaces and associated methods. Allowing each object to expose multiple interfaces allows for future upgrades without breaking existing code. In addition, the use of common interfaces should help facilitate component reuse, unit testing and make it easier to write generic reusable software.